Communication Interventions and Fear of Brown Bears: Considerations of Content and Format - Johansson, Maria; Hallgren, Lars; Flykt, Anders; Støen, Ole-Gunnar; Thelin, Linda; Frank, Jens (Frontiers in Ecology and Evolution, 2019)
Communication interventions are commonly proposed as a way to address people’s fear and negative attitudes to build tolerance in shared landscapes between humans and large carnivores. Therefore, managing authorities sometimes respond to people’s fear of brown bears (Ursus arctos) by organizing an information meeting. This study increases the understanding of the information meeting to address fear of encountering brown bears. Using a mixed-method approach the study analyzes the explicit meta-communication i.e. verbal interactions to coordinate communication between presenter and participants, the effects of the meeting on fear and fear-related variables over time, and how these effects compare with the effects of a visit to a permanent brown bear exhibition, and the effects of a guided walk with exposure to brown bears and their habitat as two alternative communication interventions. Participation in information meetings contributed to reduce self-reported fear and the effect lasted over at least six months. The information meetings were, as assessed immediately after participation, less efficient than participation in a guided walk, but more efficient than a visit to a permanent brown bear exhibition in reducing fear. The content and format of the meeting was in line with the expectations of an information meeting, e.g., the presenter dominated the initiative in the explicit meta-communication, but still allowing for misconceptions and misunderstandings to be addressed and solved. In the development of communication strategies to address fear of large carnivores, managing authorities should pay attention to details in information content and format as well as to trade-offs between the number of people reached by the intervention and the strength of the effects on fear and fear-related variables among participants.